Isolation and Analytical Characterization of Flavonoids from Indonesian Medicinal Plants: A Comprehensive Literature Review - Chandra, Devina; Tampubolon, Manuppak Irianto; Safitri, Alfi; Sihombing, Johas; Sinaga, Dianty Secilia; Marbun, Eva Diansari (NSMRJ: Nusantara Scientific Medical Research Journal, 2025)
Indonesia is recognized as one of the world’s megabiodiversity countries, possessing a vast range of medicinal plants that serve as rich sources of secondary metabolites, particularly flavonoids. These compounds are widely reported to exhibit significant pharmacological activities, including antioxidant, antidiabetic, and antibacterial effects, thereby encouraging continuous research on their isolation and identification. This study aims to systematically review the isolation and identification methods of flavonoid compounds derived from Indonesian medicinal plants, as well as to determine the most frequently reported flavonoid types and their pharmacological relevance. A literature review approach was applied by searching three scientific databases: Google Scholar, ScienceDirect, and ProQuest. Keywords used included “isolation and flavonoids” (Indonesian) and “isolation and flavonoid compounds” (English). Articles were selected based on inclusion criteria comprising publication period (2019–2024), journal accreditation, and full-text accessibility. From an initial pool of 13,400 records, only 10 articles met all eligibility criteria. The reviewed studies reported various isolation techniques, including maceration using ethanol or methanol, fractionation with ethyl acetate or water, and compound identification through Thin Layer Chromatography (TLC), UV–Vis spectrophotometry, and Nuclear Magnetic Resonance (NMR). The major flavonoids identified were quercetin, flavanone, and flavonol-3-O-galactose. Overall, Indonesian medicinal plants demonstrate strong potential as natural sources of flavonoids, with isolation and identification methods proving effective in detecting compounds with significant biological activity, particularly antioxidants.